A perspectiva contratualista na construção do consenso da sociedade na Internet - Gatto, Raquel Fortes (2016)
The thesis deals with the legitimacy of the consensus mechanisms that set rules for the society on the Internet. For a more complete understanding of the concept of Internet, it is necessary to go beyond technology: the Internet also involves legal, regulatory, economic, social and cultural development. The Internet Governance is exercised by various mechanisms for transparent, pluralist and democratic manner. Indeed, the Internet was built on the cooperation of many individuals and institutions and this pluralistic character should be reflected and preserved in the way it is managed, under penalty of losing the heart of what has been achieved successful networking: global collaboration. Overall, Western society has embraced the premise of liberties, especially in private relationships in which it operates the Internet regulation. In other words, the right only reaches society in specific cases, and what may unregulated part of the sphere of freedom. In this sense, we revisit the traditional philosophers Hobbes, Locke and Rousseau to bring a renewed view of the social contract and the safeguard of liberties and equality. We also look for John Rawls with the Theory of Justice as fairness. This is the reason why this research project proposes to investigate the characteristics of the information society under the aspects of political philosophy to defend the legitimacy of public and regulatory policy-making beyond the traditional model of composition and representation of the State. This is a bibliographic and document based study, referring to the doctrinal work, periodicals, thesis, dissertations, among others, as well as recommendations of technical standards and international agreements